Local Government Financial Ability in Doing Regional Loans in The Covid-19 Pandemic Era - Fery, Irlan (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The purpose of this study was to determine the financial capacity of local governments in making regional loans in the era of the COVID-19 pandemic. The results of the study stated that regional revenue is a source of capital, which is collected and used to finance various regional development implementation activities. The method used is Structural Equation Modeling PLS, population of this research is carried out on local government organizations, namely related sub-units in the section of the Regional Secretariat, DPRD Secretariat, Inspectorate, Service and Agency in Musi Banyuasin Regency totaling 37 people. The results show that the financing of regional autonomy requires the ability of local governments to explore sources of revenue that are not dependent on the central government. Keywords: Regional Finance; Regional Loans; Regional Revenue; Regional Development; Local Government Tujuan penelitian ini untuk mengetahui kemampuan keuangan pemerintah daerah di dalam melakukan pinjaman daerah era pandemi covid-19. Hasil penelitian menyatakan bahwa penerimaan daerah merupakan sumber modal, yang dihimpun dan dimanfaatkan untuk membiayai berbagai kegiatan pelaksanaan pembangunan daerah. Metode yang digunakan yaitu Structural Equation Modeling PLS, populasi penelitian ini dilakukan pada Organisasi Pemerintah Daerah yaitu sub-sub unit terkait pada bagian dari Sekretariat Daerah, Sekretariat DPRD, Inspektorat, Dinas dan Badan di Kabupaten Musi banyuasin berjumlah 37 orang. Hasil penelitian menunjukan bahwa pembiayaan otonomi daerah menuntut adanya kemampuan pemerintah daerah untuk menggali sumber-sumber penerimaan yang tidak tergantung kepada pemerintah pusat. Kata Kunci: Keuangan Daerah; Pinjaman Daerah; Pendapatan Daerah; Pembangunan Daerah; Pemerintah Daerah